2017
DOI: 10.1021/acsami.6b14340
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Transfer of Sequence Information into a Molecularly Imprinted Polymer for Hexakis(2,2′-bithien-5-yl) DNA Analogue Formation toward Single-Nucleotide-Polymorphism Detection

Abstract: A new strategy of simple, inexpensive, rapid, and label-free single-nucleotide-polymorphism (SNP) detection using robust chemosensors with piezomicrogravimetric, surface plasmon resonance, or capacitive impedimetry (CI) signal transduction is reported. Using these chemosensors, selective detection of a genetically relevant oligonucleotide under FIA conditions within 2 min is accomplished. An invulnerable-to-nonspecific interaction molecularly imprinted polymer (MIP) with electrochemically synthesized probes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…Our ITC measurements confirmed higher stability of the G-C pairs of the functional monomers with PNA than that of the A-T pairs. 17 Nevertheless, we still successfully and independently from matrix effects discriminated GC-rich analyte from two-and three-nucleobase mismatches with the appreciably low LOD.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Our ITC measurements confirmed higher stability of the G-C pairs of the functional monomers with PNA than that of the A-T pairs. 17 Nevertheless, we still successfully and independently from matrix effects discriminated GC-rich analyte from two-and three-nucleobase mismatches with the appreciably low LOD.…”
mentioning
confidence: 87%
“…[8][9][10][11] To minimize drawbacks of the challenging control of the density and orientation of natural probes and time-consuming optimization of the solution conditions for analyte-probe hybridization, 12 several nucleic acid analogs were designed and synthesized, [13][14][15][16] and then used as the probes. [17][18][19] Among them, peptide nucleic acids (PNAs) were selected, because of their sequenceselectivity and high affinity to complementary DNA and RNA single strands. However, they often need backbone and nucleobase modifications in order to pre-organize 20 their conformation, and then increase stability and sequence selectivity in duplex formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecularly Imprinted Polymers can serve also as a recognition tool for specific sequences of genetic information. Bartold and coworkers decided to prepare a tool for the recognizing of single nucleotide polymorphism by the imprinted polymers [ 48 ].…”
Section: Molecularly Imprinted Polymers On Piezoelectric Platformmentioning
confidence: 99%
“…QCM has a relatively rich history compared with other materials fabricated with MIPs, as the usage of QCM-biosensors can be certainly dated back to the 1980s. To date, the applications of QCM-MIP-biosensors have been widely used for different types of biological substances from micro-biological molecules like glucose [112], to macro-biological molecules, for instance, DNA [113], proteins [114,115,116], bacteria [117,118] and virus [119], furthermore it has been reported that whole cells can be also imprinted for QCM-MIP-biosensors [120,121].…”
Section: Gravimetric Sensingmentioning
confidence: 99%